Birth Weight and the Related Risks in the Mothers Delivered in the Jazan Region of Saudi Arabia - Ebtihal Elameen Eltyeb; Gassem Ali Gohal; Ali Ali Al-Makramani; Alanoud Ibrahim Mokhasha; Sara Abduh Ali; Abdullah Ahmed Almalki; Alaa Allayl; Mohammed Salih Mahfouz (Hail Journal of Health Sciences)
Introduction: Birth weight is vital to an infant’s long-term health and development. This study aims to assess the birth weight of babies born to Saudi women in the Jazan region and to determine the maternal risks influencing it. Materials and Methods: A cross-sectional study covered all the women who delivered babies in three hospitals. Data were gathered from the participants using a semi-structured questionnaire administered during a face-to-face interview, and the birth weight was measured immediately after the baby’s delivery. Results: Of 403 delivered women, 62% were between 21 and 34 years old, with 63% coming from the rural coastal part of the region. About 86% had regular antenatal care visits, ranging between 5 and 9 visits in more than half of the women. Among the participants women, 2.7% were smokers, 4.7% had hypertension, 4.7% had diabetes mellitus, and 27.5% had anemia. Regarding the neonatal outcomes, 55% gave birth to male newborns, and the mode of delivery was normal vaginal in about 69%. The gestational age was a term completing more than 37 weeks in about 92% of women, and the birth weight was 2.961 ± .51; however, 13.4% were low birth-weight newborns (<2500 g). Mother’s occupation (P = 0.007) and mother’s smoking (P = 0.047) significantly impact birth weight. In addition, maternal age >35 years is associated with low birth weight (LBW; odds ratio = 1.86, 95% confidence interval = 1.00–3.46). Conclusion: Although overall birth weight showed normal distribution, the mother’s occupation, smoking, and increased maternal age were all linked to LBW. Therefore, we recommend further studies that include more maternal risk factors.